Analysis of vegetation and ecosystem components of Mount Ciremai National Park (MCNP) with key indicators of species, density, frequency, dominance, and calculation of Important Value Index (IVI) - Aden Arif Gaffar; Aditya Marianti; Sigit Saptono; Putut Marwoto; Sunyoto Eko Nugroho (Journal of Environment and Sustainability Education, 2026)
This study aims to analyze the vegetation structure and ecosystem components of Mount Ciremai National Park (MCNP) using the parameters of density, frequency, dominance, and the Important Value Index (IVI). Data were collected across 3 observation stations using the quadrat sampling method with three-tiered plot sizes (1×1 m, 5×5 m, and 10×10 m). A total of 53 vegetation species comprising 847 individuals were identified, predominantly dominated by understory plants such as Oplismenus hirtellus and Homalomena philipinensis. The IVI analysis revealed distinct key species across different strata: H. philipinensis in the seedling stratum, Dysoxylum spectabile and D. cauliflorum in the sapling stratum, and Gurea bullata in the tree stratum, which exhibited high dominance despite a low individual count. Furthermore, environmental factors, including acidic soil pH (5.6–6.7) and stable temperatures (21–22°C), significantly influenced these distribution patterns. Notably, the stand structure was highly unbalanced, with a massive dominance of seedlings compared to saplings and trees, indicating a severe regeneration bottleneck. These findings imply that while the understory ecosystem remains stable, the forest faces a critical threat to its natural tree succession. Consequently, long term monitoring and targeted conservation strategies such as active seedling protection are urgently needed to ensure the sustainability of the forest structure in MCNP.